Reformulation of Electronic Evidence in Forex Trading Manipulation Crimes - Terra Whisnu Murti; Abdul Kholiq (Fakultas Hukum Universitas Muhammadiyah Sorong, 2025)
The aim of this study is to find the root causes of problems in legislation and weaknesses of law enforcement officials in maintaining the validity and authenticity of electronic evidence in cases of forex trading manipulation, as well as to reformulate relevant laws after identifying the root causes of the problems. The method used in this study is a normative juridical method using a legislative approach to analyze regulations related to the examination of electronic evidence and a conceptual approach in reformulating relevant regulations. Data was obtained through analysis of legislation, literature, and relevant legal doctrines. The novelty of this research lies in its focus on regulatory reform related to electronic evidence in forex trading manipulation crimes. It not only involves reformulation but also determines how the novel aspects of legal practice should be implemented. The results of this study indicate that regulations on electronic evidence, particularly Artificial Intelligence (AI) in forex trading, still need to be reformulated to accommodate technological developments, especially in terms of authenticity. The lack of knowledge of law enforcement officials in the field of technology is also a priority in determining how law enforcement officials carry out their duties as investigators in technology-based crimes. The study concludes that the existing weak regulations and the lack of knowledge of law enforcement officials in maintaining the validity of electronic evidence in cases of manipulation need to be strengthened through the reformulation of laws and regulations and the expansion of knowledge in technology for law enforcement officials. With more adaptive and comprehensive reformulation, the evidence system in forex trading cases can be more effective and provide better legal protection.